EXPLORING SYNERGIES BETWEEN SUPPLY CHAIN MANAGEMENT AND ITS CONTEMPORARY FIELDS (CAHIERS MAGELLANES-NS, 2024)
Nowadays, organisations apply Supply chain management (SCM) along with Marketing, Logistics and Information technology to achieve benefits such as operational efficiency, competitive advantages and better firm performance. An integrative literature review is applied to explore synergies between SCM and its various contemporary fields, such as Logistics, Marketing, Purchase, Sustainability and Information technology. We concluded that SCM complements the goals of its contemporary fields and vice versa. The conceptual framework proposed in the study also highlights that alignment of SCM with its contemporary fields is also conducive to organisational objectives such as operational efficiency, firm performance and competitive advantage. However, the approach applied to develop this conceptual framework has its limitations. We recommend expanding this list in the future to include subjects such as operations management, and we stress the need for empirical verification of the framework.